Teks Naratif dari Mitos Keris Ki Baru Gajah dalam Tradisi Ngrebeg - Meitridwiastiti, Anak Agung Ayu (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 25 No 1 (2018): MaretDO - 10.24843/ling.2018.v25.i01.p01, 2018)
Myth of Kris Ki New Elephant: Textual Sources in Ngrebeg Tradition in the District Kediri, Tabanan is the research conducted to analyzing  textual structure of the myth in the District of Kediri, Tabanan. The purpose of this study were: (a) to examine and describe the narrative structure of myth dagger Ki New Elephant in the Pura Luhur Pakendungan Purana, Theory used in this study is the theory of functions and semiotics. Data collection methods used are literature studies, interviews and recording. Methods of data analysis used is hermeneutics and desciptive analitic. Presentation of the results of data analysis method used is informal methods. Analysis of narrative structure associated with narrative elements that build a new myth of Kris Ki New Elephant in the Purana Pura Luhur Pakendungan the specifically related to the myth Kris Ki New Elephant and literary convention that includes genealogis,mythological then conventions of language in this case the use of the language used in the Pura Luhur Pakendungan Purana.